História (em)canto: o cancioneiro maranhense como metodologia para o ensino da história do Maranhão - OLIVEIRA, Misael Rodrigues (2023)
Starting from the premise that music is an expression present in all cultures and in all historical periods of humanity and also that this language functions as a kind of potentiator of memories associated with it, since, when we hear certain songs again, even after many years, we were able to relive facts, emotions or situations experienced at the time it was released or when we had contact with such a song. Thus, this dissertation has as its proposition the use of the cancioneiro maranhão as a methodology for teaching the History of Maranhão. The idea is to use the multiple possibilities that the song as a document can offer in the classroom environment, among which, that it can make the learning of history simultaneously playful, pleasurable and effective. This work, in addition to creating a product, as proposed by PROFHISTÓRIA, culminated in the application of it in the classroom through workshops held at the Ludovicense Baptist College.